KAJIAN TENTANG KONSUMSI, TABUNGAN DAN INVESTASI DALAM ISLAM - Sri Sutrismi Sri Sutrismi; Sudirman Sudirman; Idris Parakkasi (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This article aims to implement the theory of consumption, savings and investment in Islam. This research applies in-depth evaluation through secondary data collection methods, including library research and internet searches. Data was obtained from journals and articles that focus on Islamic consumption, savings and investment theories. The results show that consumption theory considers people's behavior in allocating their income for the consumption of goods and services. This theory highlights specific influences in the context of muslim consumer behavior, where factors such as the obligation of zakat in the concept of optimal income and the prohibition of usury influence consumption, investment and savings patterns.